Recent improvement of fish populations in the Jarfjord Mountains in northern Norway due to reduced surface water acidification - Hesthagen, Trygve; Sandlund, Odd Terje; Saksgård, Randi (2013)
Appendix 10/15 of the publication "State of the environment in the Norwegian, Finnish and Russian border area 2007" (The Finnish Environment 6/2007).